Post-merger returns in frontier markets, or how we learned to stop worrying and love the acquirers - Zaremba, Adam; Szyszka, Adam; Płotnicki, Michał; Grobelny, Przemysław (Journal of Business Economics and Management, 2018)
This study presents the results from a comprehensive out-of-sample test of long-run returns following mergers and acquisitions (M&As). Using a unique sample from 23 frontier markets of almost 800 transactions conducted during the years 1992 to 2016, we implement both cross-sectional tests and time-series examinations based on a calendar-time portfolio approach. Contrary to evidence from developed markets, the M&As in these frontier markets do not lead to abnormal underperformance of acquirers, regardless of whether they paid for the acquisition with cash or stock. The results are robust to many considerations, including subsample and subperiod analysis, alternative formation periods, different portfolio construction approaches.